2009
DOI: 10.1055/s-0029-1212086
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of TNF-α-induced insulin resistance

Abstract: There is now substantial evidence linking TNF-alpha to the presentation of insulin resistance in humans, animals and in vitro systems. We explored the relationship between TNF-alpha and insulin resistance using knockout mice deficient for either TNF-alpha or one or both of its receptors, p55 and p75. In studies of TNF-alpha-deficient knockout mice with diet-induced obesity, obese TNF-alpha knockouts responded to an exogenous dose of insulin or glucose much more efficiently than TNF-alpha wild-type animals. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
156
4
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(181 citation statements)
references
References 30 publications
4
156
4
8
Order By: Relevance
“…In animal model, several studies showed the crosslink between signaling pathways of inflammation and insulin resistance. For example, attenuated TNF‐α and TNF‐α receptor, and JNK signaling in high‐fat diet‐treated mice could reduce inflammation markers and blood sugar levels (Uysal, Wiesbrock, Marino, & Hotamisligil, 1997), and elevated the sensitivity of insulin signaling pathway (Hotamisligil, 1999; Nieto‐Vazquez et al., 2008). Therefore, reduction in inflammation by inhibiting proinflammatory cytokine production would be an alternative way to improve the insulin sensitivity of adipocytes and induce the cellular glucose uptake.…”
Section: Introductionmentioning
confidence: 99%
“…In animal model, several studies showed the crosslink between signaling pathways of inflammation and insulin resistance. For example, attenuated TNF‐α and TNF‐α receptor, and JNK signaling in high‐fat diet‐treated mice could reduce inflammation markers and blood sugar levels (Uysal, Wiesbrock, Marino, & Hotamisligil, 1997), and elevated the sensitivity of insulin signaling pathway (Hotamisligil, 1999; Nieto‐Vazquez et al., 2008). Therefore, reduction in inflammation by inhibiting proinflammatory cytokine production would be an alternative way to improve the insulin sensitivity of adipocytes and induce the cellular glucose uptake.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 5 prominent mutations spanning across 4 genes were investigated for their link with diabetic condition in an Indian resource population. The genes include the ligand inducible transcription factor-coding vitamin D receptor (VDR) gene (Ogunkolade et al, 2002), interleukin-6 (IL-6) gene (Vozarova et al, 2001), tumor necrosis factor-alpha (TNF-α) gene (Hotamisligil, 1999), and transcription factor 7-like 2 (TCF7L2) gene, a member of the T-cell-specific high-mobility group boxcontaining family of transcription factors (da Silva et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor α (TNFα) and interleukin‐6 (IL‐6) are cytokines secreted from adipose tissue as adipokines as well as from other tissues 8. Both have important roles in the induction of insulin resistance in NAFLD and type II diabetes,8, 13, 14 and iron has been shown in cell culture studies to promote a proinflammatory phenotype in macrophages 15…”
mentioning
confidence: 99%